Effects of Low-protein or High Energy Levels Diets on Layer-type Chick Juvenile Performance - Teteh, A.; Tona , K.; Aklikokou, K.; Gbeassor, M.; Buyse, J.; Decuypere, E. (International Journal of Poultry Science, 2010)
Effects of feed nutritive values on broiler performance are widely investigated. But, relationship between feed macronutrients’ levels and layer-type chicks (male and female) retains little attention. However, as for all developmental stages, starter diet composition may affect layer-type chick juvenile growth as well as physiological parameters. A total of 684 Hisex Brown layer-type chicks were studied. Chicks were divided, at random, into 3 groups with equal number of males and females: control, Low-Protein Diet (LP) and High Metabolisable Energy Diet (HME). During rearing period, feed intakes were recorded and chicks were weighed individually at the end of each week. Also, sample of chicks were used to weigh liver, at hatch and at 7, 14 and 56 day-old and to collect blood for glucose, total protein and triglyceride levels determination. Results indicate that layer-type chick growth rate, liver weight and feed efficiency were in following order HME > control > LP. With regard to chick sex, male chicks of HME and control diets grew better than female chicks from d 7 onward. But, in LP group, the weights of male and female chicks were comparable up to 49 d-old. At 7 d post-hatch, serum total protein and triglyceride levels of control chicks were higher than those of chicks of LP group while the levels of HME group were comparable to those of the two other groups. For total protein levels this trend lasted until 56 d of age. It can be concluded that low protein level of starter diet affects negatively feed efficiency and layer-type chick juvenile growth while high level of metabolisable energy improve feed efficiency and growth rate.